Pendampingan Tata Kelola Bumdes Tirto Desa Landungsari Dau Malang - Sri Wahjuni Latifah; Ahmad Waluya Jati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
Bumdes is a Village Owned Enterprise as Landungsari Village of Malang Regency has Bumdes Tirto. Of the various problems Bumdes Tirto Landungsari Village has several main problems, namely Bumdes does not have good governance, does not have long-term or short-term goals as a basis for carrying out its operational plan. Bumdes Tirto already has employees and people who work but do not have an organizational structure and job description. The impact is that Bumdes manager works alone and does not yet have a goal. The problem-solving solution offered to partners is done by training in the preparation of Organizational Structure and Job Description, socialization of the importance of work programs and training in creating work programs. Then conducted training and video creation Profile as a socialization stakeholders. Related to the improvement of the performance of the Village Market business unit, discussions have been conducted about the implementation procedures of online marketing. The purpose of this activity is the increasing knowledge of partner human resources about good governance in Bumdes and the establishment of a Blueprint consisting of long-term and short-term bumdes programs and the arrangement of bumdes profile videos as bumdes socialization media.